Diagnosis and Management of Post Traumatic Epilepsy - Ramzi, Ali; Hunaifi, Ilsa (Jurnal Biologi Tropis, 2024)
Traumatic brain injury (TBI) is a leading cause of disability and death, particularly among children and young adults, and can result in serious complications such as post-traumatic epilepsy (PTE). PTE develops after TBI and is characterized by recurrent seizures without external triggers, with the risk influenced by the location and severity of the injury. Therefore, the authors raise this topic to help improve diagnostic acuity and highlight the importance of laboratory modalities in diagnosing PTE. The literature search was conducted using Google Scholar with the keywords "Post-Traumatic Epilepsy, Biomarkers, Management, Diagnosis." Based on the inclusion and exclusion criteria, 17 publications were identified as suitable for our literature review. Diagnostic tools such as CT scans, MRIs, and EEGs are essential for assessing risk. Although antiepileptic drugs (AEDs) can reduce early seizures, they are not effective for the long-term prevention of PTE. Long-term approaches, including lamotrigine, carbamazepine, and vagus nerve stimulation (VNS), may be beneficial, but further research is needed to optimize treatment.